Purification of flavivirus VLPs by a two-step chomatographic process. Issue 47 (8th November 2019) - Lima, Túlio M.; Souza, Matheus O.; Castilho, Leda R.
Abstract: Flaviviruses are enveloped viruses with positive-sense, single-stranded RNA, which are most commonly transmitted by infected mosquitoes. Zika virus (ZIKV) and yellow fever virus (YFV) are flaviviruses that have caused significant outbreaks in the last few years. Since there is no approved vaccine against ZIKV, and since the existing YF attenuated vaccine presents disadvantages related to limited supply and to rare, but fatal adverse effects, there is an urgent need for new vaccines to control these diseases. Virus-like particles (VLPs) represent a recombinant platform to produce safe and immunogenic vaccines. Thus, based on our experience of expressing in recombinant mammalian cells VLPs of most flaviviruses circulating in the Americas, this work focused on the evaluation of chromatographic purification processes for zika and yellow-fever VLPs. The clarified cell culture supernatant was processed by a membrane-based anion-exchange chromatography and then a multimodal chromatographic step. With this process, it was possible to obtain the purified VLPs with a yield (including the clarification step) of 66.4% for zika and 68.1% for yellow fever. DNA clearance was in the range of 99.8–99.9%, providing VLP preparations that meet the WHO limit for this critical contaminant. Correct size and morphology of the purified VLPs were confirmed by dynamic light scattering (DLS) and transmission electron microscopy (TEM). The promising results obtained for both zika and yellow fever VLPs indicate that this process could be potentially applied also to VLPs of other flaviviruses.